Preservasi dan Konservasi Pustaka di Perpustakaan Proklamator Bung Hatta - Putra, Ade Darma; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This paper aims to discuss: (1) activities of preservation and conservation of library materials in the Library of Bung Hatta, (2) to prevent damage to library materials in the Library of Bung Hatta. Based on the survey results and analysis found that: (1) activities of preservation and conservation of library materials in the Library of Bung Hatta done by binding the types of volumes are volumes glue back. Besides the activities carried out by separating the library materials according to the conditions and laying back on a more regular collection, (2) to prevent damage to materials of libraries and librarians are always cleaning shelves books using the vacuum cleaner, using glass cabinets to store the collection, the humidity room with installing air conditioning, insecticide spraying, adjust room light, and to transfer the form to the collection. From the findings it is expected that library should Bung Hatta to perform maintenance of libraries damaged material as the cover is torn, book covers loose, and missing pages immediately make repairs and divert the form of library materials in addition to the scientific work in the form of a CD or flash if possible. Keywords: preservation ; conservation